2022
DOI: 10.1093/ajcn/nqac067
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure interactions with the DASH dietary pattern, sodium, and potassium: The International Study of Macro-/Micronutrients and Blood Pressure (INTERMAP)

Abstract: Background Adherence to the Dietary Approaches to Stop Hypertension (DASH) diet enhances potassium intake and reduces sodium intake and blood pressure (BP), but the underlying metabolic pathways are unclear. Objective Among free-living populations, delineate metabolic signatures associated with the DASH diet adherence, 24-hr urinary sodium and potassium excretions and the potential metabolic pathways involved. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Considering the influence of confounding factors on study outcomes and PAGln, such as age [42], SBP [43], and renal function indicated by Cr [44], we used multivariable models for further analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the influence of confounding factors on study outcomes and PAGln, such as age [42], SBP [43], and renal function indicated by Cr [44], we used multivariable models for further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Using a relatively large HF cohort, we observed a positive dose‐response relationship between plasma PAGln levels and cardiovascular outcomes. Considering the influence of confounding factors on study outcomes and PAGln, such as age [42], SBP [43], and renal function indicated by Cr [44], we used multivariable models for further analysis. After extensive adjustment for potential confounding factors, such PAGln‐cardiovascular outcome associations remained largely unchanged, suggesting that PAGln may serve as a clinically useful prognostic marker beyond the currently established risk factors (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Greater adherence to DASH diet associated with lower BP and higher potassium intake across levels of sodium intake [24 half-life of natriuretic peptides, adding a diureticlike effect to the RAAS blockade [34][35][36]. This represents an opportunity to explore potassium homeostasis by comparing this diuretic-like effect to the influence of valsartan on the serum potassium level.…”
Section: Novel Pharmacology and Potassiummentioning
confidence: 99%
“…Remarkably, his most recent publication, relating to the association of blood pressure interactions with the Dietary Approaches to Stop Hypertension (DASH) dietary pattern, sodium, and potassium, using data from the INTERMAP (International Study of Macro-/Micronutrients and Blood Pressure) that he organized and supervised appeared a few months after his death. 2…”
mentioning
confidence: 99%
“…Remarkably, his most recent publication, relating to the association of blood pressure interactions with the Dietary Approaches to Stop Hypertension (DASH) dietary pattern, sodium, and potassium, using data from the INTERMAP (International Study of Macro-/Micronutrients and Blood Pressure) that he organized and supervised appeared a few months after his death. 2 Stamler's first published article on hypertension appeared in 1949 relating to renal clearances in dogs with nephrogenic and spontaneous hypertension. 3 While Stamler's earliest research involved animal studies, he is the best remembered for his enormous body of research on the epidemiology and prevention of cardiovascular diseases, including hypertension and atherosclerosis.…”
mentioning
confidence: 99%